Relationship quality in Europe - Kenneth Aarskaug Wiik; Trude Lappegård; Renske Keizer (Statistics Norway, Research Department, 2010)
In this study, we utilize data from the first wave of the Generations and Gender Surveys to investigate relationship quality among currently married and cohabiting individuals aged 18 to 55 (N = 41, 666) in eight European countries (Bulgaria, France, Germany, Hungary, Norway, Romania, Russia, and the Netherlands). Controlling for a range of characteristics of respondents and their partners, the analyses show that cohabitors in general more often have breakup plans and are less satisfied than those married. We expected to find fewer differences between cohabitation and marriage in countries where cohabitation is widespread. Correspondingly, we find that the difference between marriage and cohabitation is largest in Russia, Romania, Germany and Bulgaria.
Keywords: Z10; Z13; Z19; 330; Marriage; Cohabitation; Relationship Quality; Europe